An energetic high-velocity compact cloud: CO−0.31+0.11. (17th September 2019) - Takekawa, Shunya; Oka, Tomoharu; Tokuyama, Sekito; Tanabe, Kyosuke; Iwata, Yuhei; Tsujimoto, Shiho; Nomura, Mariko; Shibuya, Yukihiro
ABSTRACT: We have discovered an energetic high-velocity compact cloud CO -0.31+ 0.11 in the central molecular zone of our Galaxy. CO -0.31+ 0.11 is located at a projected distance of ∼45 pc from the Galactic nucleus Sgr A*. It is characterized by its compact spatial appearance ( d ≃ 4 pc), extremely broad velocity width (Δ V > 100 km s −1 ), and high CO J = 3–2/ J = 1–0 intensity ratio. The total gas mass and kinetic energy are estimated as approximately 10^4 M_ and 10 51 erg, respectively. Two expanding bubble-like structures are found in our HCN J = 1–0 map obtained with the Nobeyama Radio Observatory 45 m telescope. In the longitude–velocity maps, CO -0.31+ 0.11 exhibits an asymmetric V shape. This kinematical structure can be well fitted by Keplerian motion on an eccentric orbit around a point mass of 2× 10^5 M_ . The enhanced CO J = 3–2/ J = 1–0 ratio is possibly attributed to the tidal compression during the pericenter passage. The model suggests that a huge mass is packed within a radius of r < 0.1 pc. The huge mass, compactness, and absence of luminous stellar counterparts may correspond to a signature of an intermediate-mass black hole (IMBH) inside. We propose a formation scenario of CO -0.31+ 0.11 in which a compact cloud has gravitationally interacted with an IMBH and a bipolar molecular outflow was driven by the past activity of the putative IMBH.